Pesantren-Based Entrepreneurial Ecosystem: Contribution of Baitul Maal Wat Tamwil - Mahmudah, Sofiyyah; Fajri AF, Muh Shadiqul; Maricar, Rezvanny (The Institute of Research and Service Community IPMAFA Pati, 2025)
This study aims to examine the role of Baitul Maal wat Tamwil (BMT) Al-Arsyadi in promoting the development of entrepreneurship within the Al-Arsyadi Pesantren environment in Samboja, East Kalimantan. The study employed a descriptive qualitative approach, utilizing data collection techniques that included in-depth interviews, participatory observation, and documentation studies. The study’s results identified three main contributions of BMT in supporting the Pesantren entrepreneurship ecosystem. First, as a provider of business capital, BMT offers access to Sharia financing that supports the sustainable development of pesantren business units. Second, as an integrated financial manager, BMT builds a transparent and accountable financial management system for pesantren. Third, BMT serves as a center for training santri (student) in entrepreneurship, offering practical and applicable Islamic value-based training programs. These findings indicate that BMT is not only a financial institution but also an agent of community-based Pesantren economic transformation. This study recommends strengthening the institutional capacity of BMT, integrating entrepreneurship curriculum into pesantren education, and replicating the model to other pesantren. This study contributes to broadening the understanding of community-based Islamic economics and the role of local institutions in building the economic independence of the community.